Hijāb, Choice, and Identity: Between Feminist Liberation and Islamic Modesty - Razia Abdullah; Showkat Hussain Dar (LECTURES: Journal of Islamic and Education Studies, 2025)
The hijāb, rooted in Islamic principles of modesty, is widely recognised as a core aspect of religious belief and practice. While the obligation of modest dress is established in Islamic sources for both men and women, interpretations of the hijāb, particularly regarding the extent of covering required for women, vary significantly across different cultural, legal, and theological contexts. Often positioned at the centre of global debates on gender and religion, the hijāb is alternately viewed as a symbol of piety, identity, resistance, or patriarchal control. This study analyses the hijāb, exploring how Muslim women understand and practice veiling within diverse socio-religious and feminist frameworks. The paper draws upon Islamic jurisprudence, feminist theory, and textual analysis to explore the Qur’anic and Hadith-based foundations of modesty, alongside the evolving discourses on veiling in both Muslim-majority societies and diaspora communities. It also considers how modesty is expected of men in Islam, though often overlooked in public discourse. Furthermore, the study investigates the impact of state policies—whether enforcing or banning the hijāb on women’s autonomy, identity formation, and public participation. The findings reveal that the hijāb cannot be reduced to a monolithic symbol. Its meanings are shaped by individual conviction, spiritual commitment, social context, and broader political dynamics. By analysing both male and female expectations of modesty, this paper contributes to a nuanced understanding of the hijāb as a multidimensional expression of Islamic faith, personal agency, and gendered identity.